Determinants of Non-Participation in Women’s Associations: A Qualitative Inquiry in Bonifacio, Misamis Occidental - Mary Rose D. Naranjo; Del Rosario, Sharra Mae; Omaña, Vincy Kaye G.; Torrion, Voltaire B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study was conducted to determine the reasons for the non-participation of members of the association's programs and activities. Using a descriptive-qualitative approach and semi-structured interviews with 20 non-participating members from four barangays, this study identified key reasons for non-participation, including familial responsibilities, political divisions, poor leadership, interpersonal conflict, and perceived unfair distribution of benefits. The analysis revealed that familial responsibilities, political issues, and leadership deficiencies were the most significant barriers to participation. Moreover, the study also identified factors that could encourage the members to actively participate in the association's programs and activities, including providing financial assistance, celebrating women's month activities, providing livelihood programs, and the wide dissemination of information by the officers in charge. The study suggests that Women's Associations must improve leadership and communication that will foster inclusivity and ensure equitable resource distribution.